Effects of non-thermal plasma on food nutrients and cereal-based raw materials (Research, Society and Development, 2022)
Non-thermal plasma (NTP) is an emerging technology that has been used for surface sterilization and food decontamination processes. However, studies have also shown promising results in modifying the characteristics of food raw materials with improvement in their physicochemical and technological properties. This review presents the different types of NTP and their effects on macronutrients, including carbohydrates, proteins, and lipids, and raw materials, such as wheat and rice flours, to modify their physicochemical characteristics. The studies have shown that NTP induced carbohydrates, lipids, and proteins oxidation, hydrolysis reactions, and pH reduction. These modifications occurred without using chemical agents, thus showing NTP as a promising alternative for use in the food industry. However, the modifications are dependent on the type of NTP, type of gas used, and complexity of the raw material composition. The challenges facing the industrial application of NTP include the mechanism of action of plasma, the regulatory aspects, scale-up, and consumer acceptance of the processed product.